Academic drift of technical VET teacher education in Germany, Sweden, and other Nordic countries - Kaiser, Franz [Verfasser] (My University, 2025)
„The academisation of vocational education and training (VET) teacher pathways, often referred to as academic drift, is a relatively recent phenomenon in Europe, with significant implications for both teacher education and VET research. This article examines the historical development of VET teacher education in Germany and Sweden, using these countries as cases to explore how political decisions and academic models have influenced their education. The study highlights the resulting tensions between the demands of academic work and the practical competencies required of VET teachers. The emphasis is on the teachers in the technical VET domain, given the distinct developmental trajectories observed in disparate disciplines, such as commerce, agriculture, and others. The research draws on document analysis, expert discussions, and workshops with VET teachers conducted during long-term research visits to Nordic countries, alongside findings from the Erasmus project ‘VETteach.’ After tracing the evolution of technical VET teacher education in Germany, the article explores the establishment of VET research as a discipline and its impact on teaching practices in the study programmes. It then shifts focus to Sweden, where the effects of academisation on VET research and teacher education are examined. A comparison with other Nordic countries provides additional context. The findings reveal that while academic drift has enhanced the theoretical underpinnings of VET, it has also created tensions between academic learning and vocational competencies, with significant implications for the future of VET teacher training and research in Europe.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; 370; Berufsschullehrer; Lehrerausbildung; Historische Entwicklung; Akademisierung; Internationaler Vergleich; Bundesrepublik Deutschland; Schweden